2018
DOI: 10.1177/1179552218801603
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Extramedullary Plasmacytoma Presenting as a Pancreatic Mass

Abstract: Extramedullary plasmacytomas (EMP) are a subcategory of plasma cell neoplasm that involves organs outside the bone marrow. Involvement of the pancreas is relatively rare, reported in only 2.3% of autopsies. Radiologic findings in plasmacytoma are nonspecific, but endoscopic ultrasound fine-needle aspiration is a fast and reliable technique to acquire a histologic sample for initial diagnosis. Recently, the use of fluorine-18 fluorodeoxyglucose PET/CT has been recommended in patients with active multiple myelom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…If these plasma cell neoplasms occur in organs outside of the bone marrow, they are referred to as extramedullary plasmacytomas, and most frequently arise in the upper respiratory tract, liver, spleen, or stomach [ 4 , 5 ]. Although rare, these tumors may be found in the pancreas, accounting for only 2.3% of extramedullary plasmacytoma cases [ 6 , 7 ]. Furthermore, approximately 80% of these tumors occur in the pancreatic head [2] and can be primary or secondary to MM, depending on blood serum markers or bone marrow involvement [8] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If these plasma cell neoplasms occur in organs outside of the bone marrow, they are referred to as extramedullary plasmacytomas, and most frequently arise in the upper respiratory tract, liver, spleen, or stomach [ 4 , 5 ]. Although rare, these tumors may be found in the pancreas, accounting for only 2.3% of extramedullary plasmacytoma cases [ 6 , 7 ]. Furthermore, approximately 80% of these tumors occur in the pancreatic head [2] and can be primary or secondary to MM, depending on blood serum markers or bone marrow involvement [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, approximately 80% of these tumors occur in the pancreatic head [2] and can be primary or secondary to MM, depending on blood serum markers or bone marrow involvement [8] . Solitary plasmacytomas of the pancreas are associated with poor prognoses, especially in patients over the age of 50 with a tumor size above 4 cm [7] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,22 Several studies have shown that secondary pancreatic plasmacytoma is associated with a poor prognosis, high mortality and shortened overall survival. 4,38,42…”
mentioning
confidence: 99%